Cs3Bi2Br9 / BiOCl composite material as well as preparation method and application thereof
By preparing the Cs3Bi2Br9/BiOCl composite, the problem of poor response of bismuth oxychloride photocatalyst under the full spectrum was solved, and excellent carbon dioxide reduction performance under the full spectrum was achieved.
Patent Information
- Application Number
- CN202411813059.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The band gap of existing bismuth oxychloride photocatalysts is wide, resulting in poor performance of photocatalytic carbon dioxide reduction under the full spectrum.
BiOCl was prepared by solvothermal method using Cs3Bi2Br9/BiOCl composite, and it was added to the dimethyl sulfoxide solution of CsBr-BiBr3 and stirred to disperse it, and then dried in a drying oven, and the Cs3Bi2Br9/BiOCl composite was obtained by dropwise addition of isopropanol.
The composite material has an S-shaped heterostructure, a suitable energy band structure, forming a built-in electric field, which is conducive to the migration and separation of carriers, significantly improves the photocatalytic capacity, and can successfully reduce carbon dioxide into carbon monoxide and methane gas under the full spectrum.
Smart Images

Figure CN119588382A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a Cs3Bi2Br9 / BiOCl composite material and a preparation method and application thereof. Background Art
[0002] Against the backdrop of increasingly severe global environmental problems, the emission of greenhouse gas carbon dioxide has become one of the problems that need to be solved urgently. Photocatalytic materials refer to a type of semiconductor catalyst material that is required for photochemical reactions to occur under the action of light. Photocatalytic materials can convert carbon dioxide into renewable energy for subsequent use under the irradiation of sunlight. It has become a green technology to solve environmental problems in recent years and is a very promising method for treating carbon dioxide gas.
[0003] Bismuth oxychloride (BiOCl) is a non-toxic and corrosion-resistant photocatalytic material with a unique layered sandwich structure consisting of a double chloride ion layer and [Bi2O2] 2+ The layers are alternately composed, and there is an electrostatic field in the middle, which is conducive to the migration and separation of electrons and holes (eh), so it has attracted widespread attention in the field of photocatalytic carbon dioxide reduction.
[0004] However, the applicant has found that the prior art has at least the following technical problems:
[0005] The band gap of bismuth oxychloride photocatalyst is relatively wide, about 3.6 eV, so the performance of photocatalytic carbon dioxide reduction under the full spectrum is poor. Therefore, how to provide a bismuth oxychloride-based heterojunction photocatalyst with excellent carbon dioxide reduction performance under the full spectrum is currently challenging and valuable for those skilled in the art. Summary of the invention
[0006] The purpose of the present application is to provide a Cs3Bi2Br9 / BiOCl composite material and its preparation method and application, aiming to solve the technical problems existing in the prior art that bismuth oxychloride photocatalyst has poor response to the full spectrum and low efficiency of photocatalytic carbon dioxide reduction.
[0007] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0008] In a first aspect, the present application provides a method for preparing a Cs3Bi2Br9 / BiOCl composite material, comprising the following steps:
[0009] Step S1: preparing BiOCl: bismuth nitrate pentahydrate and acetic acid are mixed in a certain proportion and stirred to be uniformly mixed until dissolved, then methanol and D(+)-glucosamine hydrochloride are added, the mixed solution is transferred into an autoclave for reaction, after cooling to room temperature, the sample is collected by centrifugation, washed with water and ethanol in turn, and then dried in a drying oven to obtain BiOCl;
[0010] Step S2: preparing a CsBr-BiBr3 solution: adding cesium bromide and bismuth bromide into dimethyl sulfoxide, stirring to dissolve them, and obtaining a CsBr-BiBr3 solution;
[0011] Step S3: adding the BiOCl obtained in step S1 to the CsBr-BiBr3 solution obtained in step S2 in a certain proportion, stirring to mix them evenly, and then placing the mixed solution in a drying oven to dry;
[0012] Step S4: Take the powder obtained in step S3, add isopropanol solution drop by drop into the powder under stirring conditions, react for 0.5 to 2 hours after the addition is completed, centrifuge the obtained solution to collect the sample, wash the sample with ethanol, centrifuge the washed sample, and dry it in a drying oven to obtain a Cs3Bi2Br9 / BiOCl composite material.
[0013] In one or more embodiments of the present application, in the step of preparing BiOCl in step S1, the mass ratio of the bismuth nitrate pentahydrate to the D(+)-glucosamine hydrochloride is 5.0:1.5, the amount of acetic acid is 10-50 ml, the amount of methanol is 100-140 ml, and the temperature of the thermal reaction in the autoclave is 160-180°C.
[0014] In one or more embodiments of the present application, in the step of preparing the CsBr-BiBr3 solution in step S2, the mass ratio of the cesium bromide to the bismuth bromide is 0.096:0.1345, and the amount of the dimethyl sulfoxide is 5-15 ml.
[0015] In one or more embodiments of the present application, in step S3, the mass amount of BiOCl is 0.15-0.35 g, the amount of CsBr-BiBr3 solution is 1 ml-4 ml, the stirring time is 30-90 minutes, and the drying temperature in the drying oven is 50-90°C.
[0016] In one or more embodiments of the present application, in step S4, the amount of the isopropanol solution is 3 ml to 7 ml, the stirring time is 30 to 90 minutes, and the drying temperature in the drying oven is 50 to 90°C.
[0017] In a second aspect, the present application provides a Cs3Bi2Br9 / BiOCl composite material, wherein the Cs3Bi2Br9 / BiOCl composite material is prepared by the preparation method described in the first aspect.
[0018] In a third aspect, the present application also provides an application of the Cs3Bi2Br9 / BiOCl composite material described in the second aspect in the photocatalytic reduction of carbon dioxide.
[0019] Based on the above technical solution, the Cs3Bi2Br9 / BiOCl composite material of the present invention and its preparation method and application have at least the following technical effects:
[0020] The present application first prepares BiOCl by a solvothermal method, then adds BiOCl to a dimethyl sulfoxide solution of CsBr-BiBr3 and stirs it to disperse it, and then dries it in a drying oven; drips isopropyl alcohol (IPA) drop by drop into the obtained solid, and after the reaction is complete, collects the sample by centrifugation, washes the sample with ethanol, collects the washed sample by centrifugation, and dries it in a drying oven to obtain a Cs3Bi2Br9 / BiOCl composite material. The preparation method of the Cs3Bi2Br9 / BiOCl composite material of the present application has a simple operation process, and the prepared material has a high yield and low cost. The Cs3Bi2Br9 / BiOCl composite material prepared by the preparation method of the present application is a photocatalytic material with an S-type heterostructure, which has a uniform distribution of cesium, bismuth, bromine, oxygen and chlorine elements. Cs3Bi2Br9 and BiOCl have suitable energy band structures. After forming a heterojunction, the difference in Fermi levels causes a spontaneous formation of a built-in electric field between the materials, which is beneficial to the migration of carriers. In addition, the ineffective carriers in the S-type heterojunction tend to recombine at the heterojunction interface, retaining the high redox ability of the composite material. Compared with single Cs3Bi2Br9 or BiOCl, the photocatalytic ability of the Cs3Bi2Br9 composite material is greatly improved. The prepared Cs3Bi2Br9 composite material can successfully reduce carbon dioxide to carbon monoxide and methane gas under broad-spectrum light, and has photocatalytic ability under the full spectrum. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 This is the XRD pattern of the Cs3Bi2Br9 / BiOCl composite material prepared in Example 5.
[0023] Figure 2 The following are scanning electron microscope images of the BiOCl material prepared in Example 1, the Cs3Bi2Br9 material prepared in Example 2, the Cs3Bi2Br9 / BiOCl materials of different proportions prepared in Examples 3-5, and the transmission electron microscope image and element distribution diagram of the Cs3Bi2Br9 / BiOCl material prepared in Example 4. Figure 2 (a) is a scanning electron microscope image of the BiOCl material in Example 1; Figure 2 (b) is a scanning electron microscope image of the Cs3Bi2Br9 material obtained in Example 2; Figure 2 (c) is a scanning electron microscope image of the Cs3Bi2Br9 / BiOCl material obtained in Example 3; Figure 2 (d) is a scanning electron micrograph of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4;
[0024] Figure 2 (e) is a scanning electron microscope image of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 5, Figure 2 (f) is a low-magnification transmission electron microscopy image of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4; Figure 2 (g) to Figure 2 (k) is the element distribution diagram of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4, Figure 2 (l) is a high-resolution transmission electron microscopy image of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4.
[0025] Figure 3 The photocatalytic carbon dioxide reduction performance diagram of the BiOCl material prepared in Example 1, the Cs3Bi2Br9 material prepared in Example 2, and the Cs3Bi2Br9 / BiOCl materials of different ratios prepared in Examples 3-5.
[0026] Figure 4 In-situ X-ray photoelectron spectroscopy analysis and electron spin resonance spectrum of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4. DETAILED DESCRIPTION
[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail in conjunction with the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0028] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0029] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0030] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0031] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0032] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0033] Raw materials and their sources
[0034] Bismuth nitrate pentahydrate: Bi(NO3)3·5H2O, analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0035] Acetic acid: CH3COOH, analytical grade, Chengdu Kelong Chemical Co., Ltd.
[0036] Methanol: CH3OH, analytical grade, Chengdu Kelong Chemical Co., Ltd.
[0037] D(+)-Glucosamine hydrochloride: C6H 13 NO5·HCl, analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0038] Cesium bromide: CsBr, analytical grade, from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0039] Bismuth bromide: BiBr3, analytical grade, from Shanghai Myril Biochemical Technology Co., Ltd.
[0040] Dimethyl sulfoxide: C2H6OS, analytical grade, Chengdu Kelong Chemical Co., Ltd.
[0041] Isopropanol: C3H8O, analytical grade, Chengdu Kelong Chemical Co., Ltd.
[0042] The present application provides a method for preparing a Cs3Bi2Br9 / BiOCl composite material, and the specific steps are as follows:
[0043] Step S1: Preparation of BiOCl: 4.852 g of bismuth nitrate pentahydrate and 10-50 ml of acetic acid are mixed in a certain proportion and stirred to make them uniformly mixed until dissolved, then 100-140 ml of methanol and 1.510 g of D(+)-glucosamine hydrochloride are added, and the mixed solution is transferred into an autoclave for reaction at a temperature of 160-180° C. After cooling to room temperature, the sample is collected by centrifugation, washed with water and ethanol in turn, and dried in a drying oven to obtain BiOCl.
[0044] Step S2: Prepare a CsBr-BiBr3 solution by adding 0.096 g of cesium bromide and 0.1345 g of bismuth bromide into 5-15 ml of dimethyl sulfoxide, stirring to dissolve the mixture, and obtaining a CsBr-BiBr3 solution.
[0045] Step S3: adding the BiOCl obtained in step S1 to the CsBr-BiBr3 solution obtained in step S2 in proportion, stirring to make it evenly mixed, and then putting the mixed solution into a drying oven for drying; the mass amount of BiOCl is 0.15-0.35g, the amount of CsBr-BiBr3 solution is 1ml-4ml, the stirring time is 30-90 minutes, and the drying temperature in the drying oven is 50-90°C.
[0046] Step S4: Add 3 ml to 7 ml of isopropanol dropwise into the powder obtained in step S3 under stirring, react for 0.5 to 2 hours after the addition is completed, centrifuge the obtained solution to collect the sample, wash the sample with ethanol, centrifuge the washed sample, and dry it in a drying oven to obtain a Cs3Bi2Br9 / BiOCl composite material. Preferably, in the operation of centrifugation to collect the sample, the speed of the centrifuge used is 13000 rpm, the stirring time is 30 to 90 minutes, and the drying temperature in the drying oven is 50 to 90°C.
[0047] The technical solution of the present application is described in detail below in conjunction with specific embodiments.
[0048] Example 1
[0049] This embodiment 1 provides a method for preparing a BiOCl material, comprising the following steps:
[0050] S1: Add 4.852 g of bismuth nitrate pentahydrate to 30 mL of acetic acid and stir to mix evenly until completely dissolved. Then add 120 mL of methanol and 1.510 g of D(+)-glucosamine hydrochloride to the mixed solution and continue magnetic stirring for 1 hour;
[0051] S2: The solution obtained in step S1 was transferred to a Teflon-lined stainless steel autoclave; and the reaction was carried out at 180° C. for 5 hours;
[0052] S3: After the solution is cooled to room temperature, the sample is collected by centrifugation, and the sample is washed with deionized water at least three times, the washed sample is collected by centrifugation, and dried in a drying oven at 70° C. overnight to obtain the prepared BiOCl material. In the operation of collecting the sample by centrifugation, the speed of the centrifuge used is 13,000 rpm.
[0053] Example 2
[0054] This embodiment 2 provides a method for preparing a Cs3Bi2Br9 photocatalytic material, comprising the following steps:
[0055] S1: Add 0.384g of CsBr and 0.538g of BiBr3 into 10mL of dimethyl sulfoxide and stir to mix well. Then slowly add the solution into 50mL of isopropanol and react for 1 hour under magnetic stirring;
[0056] S2: The solution obtained in step S1 is centrifuged to collect a sample, washed with ethanol, and dried in a drying oven at 70°C overnight. The prepared material is Cs3Bi2Br9. During the operation of centrifugation to collect the sample, the speed of the centrifuge used is 13,000 rpm.
[0057] Example 3
[0058] This embodiment 3 provides a method for preparing a Cs3Bi2Br9 / BiOCl photocatalytic material, comprising the following steps:
[0059] S1: 0.25 g of BiOCl was added to 2 mL of CsBr-BiBr3 solution, stirred at room temperature for 1 hour, and then the above system was dried in a drying oven at 70 °C.
[0060] Among them, the preparation method of BiOCl includes: adding 4.852g of bismuth nitrate pentahydrate to 30mL of acetic acid and stirring until completely dissolved. Then, 120mL of methanol and 1.510g of D(+)-glucosamine hydrochloride are added to the mixed solution, and then the mixed solution is transferred to an autoclave for reaction, and the solvent thermal reaction is carried out at 180°C for 5 hours; after cooling to room temperature, the sample is collected by centrifugation, washed with water and ethanol, and dried in a drying oven at 70°C to obtain BiOCl. The preparation method of CsBr-BiBr3 solution includes: adding 0.096g of cesium bromide and 0.1345g of bismuth bromide to 10mL of dimethyl sulfoxide, stirring to dissolve it, and obtaining CsBr-BiBr3 solution.
[0061] S2: The powder obtained in step S1 is transferred to a beaker, and 5 mL of isopropanol is dripped into the powder dropwise under stirring. After the dripping is completed, the reaction is carried out for 1 hour, and the obtained solution is centrifuged to collect the sample, and the sample is washed with ethanol, and the washed sample is centrifuged and collected, and dried in a drying oven at a drying temperature of 70° C. to obtain a Cs3Bi2Br9 / BiOCl composite material. In the operation of centrifugation to collect the sample, the speed of the centrifuge used is 13,000 rpm.
[0062] Example 4
[0063] This embodiment 4 provides a method for preparing a Cs3Bi2Br9 / BiOCl photocatalytic material, comprising the following steps:
[0064] S1: 0.25 g of BiOCl was added to 3 mL of CsBr-BiBr3 solution, stirred at room temperature for 1 hour, and then the above system was dried in a drying oven at 70 °C.
[0065] Among them, the preparation method of BiOCl includes: adding 4.852g of bismuth nitrate pentahydrate to 30mL of acetic acid and stirring until completely dissolved. Then, 120mL of methanol and 1.510g of D(+)-glucosamine hydrochloride are added to the mixed solution, and then the mixed solution is transferred to an autoclave for reaction, and the solvent thermal reaction is carried out at 180°C for 5 hours; after cooling to room temperature, the sample is collected by centrifugation, washed with water and ethanol, and dried in a drying oven at 70°C to obtain BiOCl. The preparation method of CsBr-BiBr3 solution includes: adding 0.096g of cesium bromide and 0.1345g of bismuth bromide to 10mL of dimethyl sulfoxide, stirring to dissolve it, and obtaining CsBr-BiBr3 solution.
[0066] S2: The powder obtained in step S1 is transferred to a beaker, and 5 mL of isopropanol is dripped into the powder dropwise under stirring. After the dripping is completed, the reaction is carried out for 1 hour, and the obtained solution is centrifuged to collect the sample, and the sample is washed with ethanol, and the washed sample is centrifuged and collected, and dried in a drying oven at a drying temperature of 70° C. to obtain a Cs3Bi2Br9 / BiOCl composite material. In the operation of centrifugation to collect the sample, the speed of the centrifuge used is 13,000 rpm.
[0067] Example 5
[0068] This embodiment 5 provides a method for preparing a Cs3Bi2Br9 / BiOCl photocatalytic material, comprising the following steps:
[0069] S1: 0.25 g of BiOCl was added to 4 mL of the mixed solution of CsBr-BiBr3, stirred at room temperature for 1 hour, and then the above system was dried in a drying oven at 70 °C.
[0070] Among them, the preparation method of BiOCl includes: adding 4.852g of bismuth nitrate pentahydrate to 30mL of acetic acid and stirring until completely dissolved. Then, 120mL of methanol and 1.510g of D(+)-glucosamine hydrochloride are added to the mixed solution, and then the mixed solution is transferred to an autoclave for reaction, and the solvent thermal reaction is carried out at 180°C for 5 hours; after cooling to room temperature, the sample is collected by centrifugation, washed with water and ethanol, and dried in a drying oven at 70°C to obtain BiOCl. The preparation method of CsBr-BiBr3 solution includes: adding 0.096g of cesium bromide and 0.1345g of bismuth bromide to 10mL of dimethyl sulfoxide, stirring to dissolve it, and obtaining CsBr-BiBr3 solution.
[0071] S2: The powder obtained in step S1 is transferred to a beaker, and 5 mL of isopropanol is dripped into the powder dropwise under stirring. After the dripping is completed, the reaction is carried out for 1 hour, and the obtained solution is centrifuged to collect the sample, and the sample is washed with ethanol, and the washed sample is centrifuged and collected, and dried in a drying oven at a drying temperature of 70° C. to obtain a Cs3Bi2Br9 / BiOCl composite material. In the operation of centrifugation to collect the sample, the speed of the centrifuge used is 13,000 rpm.
[0072] Example 6
[0073] This Example 6 provides an experiment on photocatalytic reduction of carbon dioxide using the products prepared in Examples 1 to 5.
[0074] Specific:
[0075] 10 mg of each product prepared in Example 1, Example 2, Example 3, Example 4, and Example 5 was uniformly dispersed in a 25 mL beaker. The beaker was placed in the center of a 200 mL quartz reactor, and 50 μL of water was dripped into the edge of the reactor. The reactor was sealed and bubbled with high-purity CO2 for 20 min to fill the reactor with CO2 gas. A photocatalytic CO2 reduction reaction was carried out under the conditions of a 300 W xenon lamp as the light source and an AM 1.5G filter, and the product was analyzed by gas chromatography.
[0076] Results Figures 1 to 3 As shown, Figure 1 to Figure 3 The pictures are obtained by characterizing the BiOCl material prepared in Example 1, the Cs3Bi2Br9 material prepared in Example 2, and the Cs3Bi2Br9 / BiOCl materials prepared in Examples 3 to 5.
[0077] in:
[0078] Figure 1 This is the XRD of the Cs3Bi2Br9 / BiOCl material prepared in Example 5. Figure 1 The XRD analysis results of the sample, wherein the XRD spectrum reveals the crystal structure of the prepared material, indicating that the material contains BiOCl and Cs3Bi2Br9 substances and has good crystallinity.
[0079] Figure 2 The following are scanning electron microscope images of the BiOCl material prepared in Example 1, the Cs3Bi2Br9 material prepared in Example 2, the Cs3Bi2Br9 / BiOCl material prepared in Examples 3 to 5, and the transmission and surface distribution images of the Cs3Bi2Br9 / BiOCl material prepared in Example 4. Figure 2 (a) is a scanning electron microscope image of the BiOCl material in Example 1; Figure 2(b) is a scanning electron microscope image of the Cs3Bi2Br9 material obtained in Example 2; Figure 2 (c) is a scanning electron microscope image of the Cs3Bi2Br9 / BiOCl material obtained in Example 3; Figure 2 (d) is a scanning electron micrograph of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4; Figure 2 (e) is a scanning electron microscope image of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 5. Figure 2 As shown in (a), it can be seen that BiOCl is spherical and has a flower-like structure on the surface. Figure 2 As shown in (b), it can be seen that Cs3Bi2Br9 presents irregular particle morphology, such as Figure 2 (c) to Figure 2 As shown in (e), the Cs3Bi2Br9 / BiOCl composite material has a spherical morphology with fine particles growing on the surface, indicating that the flower-like structure of BiOCl will limit the growth of Cs3Bi2Br9 particles.
[0080] Figure 2 (f) is a low-magnification transmission electron microscopy image of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4; Figure 2 (g) to Figure 2 (k) is the element distribution diagram of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4. It can be seen that the elements Bi, O, Cl, Cs, and Br are evenly distributed. Figure 2 (l) is a high-resolution transmission electron microscopy image of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4. It can be seen that lattices representing Cs3Bi2Br9 and BiOCl appear in the composite material, indicating the successful synthesis of the heterojunction.
[0081] Figure 3 The photocatalytic carbon dioxide reduction performance diagram of BiOCl prepared in Example 1, Cs3Bi2Br9 prepared in Example 2, and Cs3Bi2Br9 / BiOCl materials prepared in Examples 3 to 5. Figure 3 It can be seen that the Cs3Bi2Br9 / BiOCl material prepared in Example 4 has the best photocatalytic reduction performance for carbon dioxide, and the rate of generating CO is 14.10 μmol·g -1 ·h -1 , higher than BiOCl material and Cs3Bi2Br9 material.
[0082] Figure 4 The in-situ X-ray photoelectron spectroscopy analysis and electron spin resonance spectrum of the Cs3Bi2Br9 / BiOCl composite material obtained in Example 4 are shown in FIG. Figure 4 (a) is the Cs element fine spectrum of Example 4; Figure 4 (b) is the Cl element fine spectrum of Example 4. Figure 4 (a) with Figure 4 (b) It can be seen that after BiOCl and Cs3Bi2Br9 come into contact, there is a built-in electric field in the heterojunction, which is conducive to the internal charge migration. Under irradiation, the electrons in Cs3Bi2Br9 / BiOCl are transferred from BiOCl to Cs3Bi2Br9. Figure 4 (c) is the DMPO-·OH spectrum of Example 4; Figure 4 (d) DMPO-·O2 of Example 4 - Spectrum. Figure 4 (c) and Figure 4 (d) It can be seen that more photoexcited holes and electrons are accumulated in the valence band of BiOCl and the conduction band of Cs3Bi2Br9 in the Cs3Bi2Br9 / BiOCl composite material, respectively. Combined with the results of in situ X-ray photoelectron spectroscopy analysis, it can be concluded that the carrier migration mechanism in the Cs3Bi2Br9 / BiOCl composite material is an S-type mechanism.
[0083] Therefore, the preparation method of the present application designs and prepares a new S-type heterojunction Cs3Bi2Br9 / BiOCl by an impregnation method, wherein BiOCl is in the shape of a flower ball of stacked nanosheets, and Cs3Bi2Br9 grows on the surface of BiOCl in the form of irregular particles. The results show that the heterostructure formed by Cs3Bi2Br9 / BiOCl can generate a built-in electric field at the interface, which is beneficial to the separation of carriers. In addition, due to the unique migration mechanism of S-type carriers, the invalid electrons in the conduction band of BiOCl and the holes in the valence band of Cs3Bi2Br9 recombine at the interface. This recombination of invalid carriers effectively retains the redox ability of the conduction band of Cs3Bi2Br9 and the valence band of BiOCl. The composite material exhibits excellent photocatalytic activity under the irradiation of simulated sunlight. The prepared Cs3Bi2Br9 / BiOCl material exhibits a CO generation rate of 14.10 μmol·g for the photocatalytic reduction of carbon dioxide. -1 ·h -1 , which is much higher than that of BiOCl and Cs3Bi2Br9. These research results can provide a new platform for the design, manufacture and application of S-type photocatalysts with excellent performance under broadband light, and have potential utilization value in carbon dioxide reduction.
[0084] The Cs3Bi2Br9 / BiOCl composite material prepared in this application can be applied to products in the photocatalytic reduction of carbon dioxide.
[0085] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a Cs3Bi2Br9 / BiOCl composite material, characterized in that: The steps include: Step S1: preparing BiOCl: bismuth nitrate pentahydrate and acetic acid are mixed in a certain proportion and stirred to be uniformly mixed until dissolved, then methanol and D(+)-glucosamine hydrochloride are added, the mixed solution is transferred into an autoclave for reaction, after cooling to room temperature, the sample is collected by centrifugation, washed with water and ethanol in turn, and then dried in a drying oven to obtain BiOCl; Step S2: preparing a CsBr-BiBr3 solution: adding cesium bromide and bismuth bromide into dimethyl sulfoxide, stirring to dissolve them, and obtaining a CsBr-BiBr3 solution; Step S3: adding the BiOCl obtained in step S1 to the CsBr-BiBr3 solution obtained in step S2 in a certain proportion, stirring to mix them evenly, and then placing the mixed solution in a drying oven to dry; Step S4: Take the powder obtained in step S3, add isopropanol solution drop by drop into the powder under stirring conditions, react for 0.5 to 2 hours after the addition is completed, centrifuge the obtained solution to collect the sample, wash the sample with ethanol, centrifuge the washed sample, and dry it in a drying oven to obtain a Cs3Bi2Br9 / BiOCl composite material.
2. The preparation method according to claim 1, characterized in that: In the step of preparing BiOCl in step S1, the mass ratio of the bismuth nitrate pentahydrate and the D(+)-glucosamine hydrochloride is: 4.852:1.510, the amount of acetic acid used is 10-50 ml, the amount of methanol used is 100-140 ml, and the temperature of the thermal reaction in the autoclave is 160-180°C.
3. The preparation method according to claim 1, characterized in that: In the step of preparing the CsBr-BiBr3 solution in step S2, the mass ratio of the cesium bromide to the bismuth bromide is 0.096:0.1345, and the amount of dimethyl sulfoxide is 5 to 15 ml.
4. The preparation method according to claim 1, characterized in that: In step S3, the mass amount of BiOCl is 0.15-0.35 g, the amount of CsBr-BiBr3 solution is 1 ml-4 ml, the stirring time is 30-90 minutes, and the drying temperature in the drying oven is 50-90°C.
5. The preparation method according to claim 1, characterized in that: In step S4, the amount of the isopropanol solution is 3 ml to 7 ml, the stirring time is 30 to 90 minutes, and the drying temperature in the drying oven is 50 to 90°C.
6. A Cs3Bi2Br9 / BiOCl composite material, characterized in that: The Cs3Bi2Br9 / BiOCl composite material is prepared by the preparation method described in any one of claims 1 to 5.
7. Use of the Cs3Bi2Br9 / BiOCl composite material according to claim 6 in photocatalytic reduction of carbon dioxide.
Citation Information
Patent Citations
Bi2MoO6atZnIn2S4 graded S-type heterostructure photocatalyst and preparation method thereof
CN117138802A
CsPbBr3 quantum dot / BiOCl heterojunction photocatalyst for CO2 reduction and preparation method of CsPbBr3 quantum dot / BiOCl heterojunction photocatalyst
CN118022784A
Photocatalyst for carbon dioxide reduction, and method for producing methane
JP2022064097A